Personal, financial and job-related factors affecting Malaysian employees’ presenteeism in the service sector - Abd. Rahim, Husniyah; Sabri, Mohamad Fazli; Mat Rahim, Fatin Farwizah; Othman, Mohd. Amim; Magli, Amirah Shazana (Human Resource Management Academic Research Society, 2020)
In paving success of an organization, job productivity among service sector employees is crucial. High management cost may be incurred by organizations in the long run when ignoring the factors contributing to a better job productivity. The job productivity concept is represented by absenteeism and presenteeism however the focus of this study is on presenteeism which is a state of behaviour where employees are present for work regardless of their current state of physical or psychological health. Personal, financial and job-related factors are determined their potential contributions for presenteeism among Malaysian employees in the civil service sector. Concentrating on service sector due to its main contribution on Malaysia gross domestic product (GDP), a cross-sectional survey and multi-stage random sampling was conducted resulting in 470 sets of data being analysed. The outcome of the study revealed factors such as locus control, materialism, work-life balance, financial stress and health as the factors that significantly affecting presenteeism of the service sector employees. The results will enable employers to develop appropriate intervention programs in enhancing the quality of personal, financial and job-related factors of the employees. Better services are expected to be offered by civil service agencies to the public as the outcomes are beneficial for both parties that are the customers and employees. Efficient time use by various parties would be the consequences of this action thus enabling the growth in economy.